An aberrant mediastinal medial basal segmental pulmonary artery (A7a) in a patient with lung cancer: a case report - Takase, Yoshiaki (Surg Case Rep, 2021)
BACKGROUND: Mediastinal branching of the A7a from the right main pulmonary artery (PA) is extremely rare. Herein, we report a patient with an aberrant mediastinal A7a who underwent right basal segmentectomy for lung cancer. CASE PRESENTATION: A 73-year-old man was referred to our department for a right lower lobe nodule measuring 18 mm in diameter on computed tomography (CT). Three-dimensional (3D) CT revealed mediastinal A7a branching from the right main PA. As the patient had undergone colectomy for advanced ascending colon cancer, the nodule was suspected to be a metastasis from the colon primary, and thus, basal segmentectomy of the right lung was performed. Intraoperatively, the A7a was observed behind the V4+5 and middle lobe bronchus. The pathological diagnosis was combined small cell carcinoma with an adenocarcinoma component (p-T1cN0M0, stage IA3). The patient subsequently received adjuvant chemotherapy for colon cancer. At 1-year postoperative follow-up, there was no evidence of disease. CONCLUSION: This is the first report describing an aberrant mediastinal A7a branching from the right main PA. It is important to obtain accurate information about variations of the PA using 3D-CT for safe anatomical pulmonary resection.